Improving productivity with delayed differentiation for EV production - T Thanesvaran (Nanyang Technological University, 2022)
The automotive industry is currently going through a revolution. It is the dawn of the electrification era and mass manufacturers of automobiles are racing to get their share of the new electric vehicle (EV) market. Auto manufacturers are announcing new lineups, with some even announcing discontinuing their fuel-burning models.